ANALISIS KOMPARATIF TENTANG KONSEP PENDIDIKAN ANAK MENURUT IBNU QAYYIM AL-JAUZIYAH DAN AL-GHAZALI: IMPLIKASINYA TERHADAP PENDIDIKAN AGAMA ISLAM KONTEMPORER - Imron Rossidy (lp2m-uin malang, 2010)
The concept of child education nowadays mainly adopted from the West which is developed base on secular-positivistic-materialistic worldview although Muslim scholars already developed the concept of child education in past period. However, the researcher identify the gap in Islamic intellectual heritage regarding prior studies on the concept of Ibn Qayyim and Al-Ghazali is in partial and no study was conducted in comprehensive manner with regard to Ibnu Qayyim and Al-Ghazali conception on child education and its implication on contemporary Islamic education.The aim of this study is to compare the concept of Ibn Qayyim and Al-Ghazali on child education and reveals its implications for contemporary Islamic education.This research is a library research. The data gathering technique used is documentation. Data analysis utilize in this research are content, linguistic, concept, history and comparative analysis. The results of this research indicate that the concept of child education according to Ibnu Qayyim and Al-Ghazali have certain degree of similarity than its difference. Their concept developed profoundly insight on human nature, knowledge and values derived from Al-Quran and As-Sunnah. Ibnu Qayyim conception on child education classify as perennials-essentials salafi, where is Al-Ghazali conception clasified as perennials-essentials mazhabi. Meanwhile, the concept of Ibnu Qayyim and Al-Ghazali on child nature categories is considered as theory convergences Theo centrism. The mayor differences between two conception lays on utilisation certain key term, some aspects of education discuss separately by Ibnu Qayyim while Al-Ghazali tends to use more general term.